The reform of proportional representation and the party fragmentation of the Brazilian Chamber of Deputies (2014-2022) - Nicolau, Jairo (2023)
The proportional system in force in Brazil went through a long period of stability, keeping its operating mechanisms intact. Between 2015 and 2021, however, the National Congress approved a series of changes that affected the way votes were counted and the dynamics of competition in elections for councilors and deputies. This article has two objectives. The first is to summarize these new rules. The second is to analyze the results of the elections for the Chamber of Deputies in 2014, 2018 and 2022 at the state level. The selection of the three elections is due to the fact that they used different electoral rules. In general terms, we observed that liberal norms contributed to increasing party fragmentation in the 2018 election, and the end of coalitions played a decisive role in the significant reduction in fragmentation in the 2022 elections.